Application of Linear and Non-linear Programming Model to Assess the Sustainability of Water Resources in Agricultural Patterns - Seyed Abolghasem Mortazavi; Reza Hezareh; Sina Ahmadi Kaliji; Samira Shayan Mehr (International Journal of Agricultural Management and Development, 2014)
Water resources sustainability is one of the major issues in the agricultural sustainability. In this study sustainability of water resources has been investigated by use of linear and non-linear models in six models based on optimal utilization of water resources in the north parts farms of Iran because of incorrect use of agricultural water resources, from 2011 to 2012. Also “gross margin per a unit of water consumption” and “employment per a unit of water consumption” are used as indicators for assessing the sustainability of cropping patterns. The results show that cropping pattern of fractional goal programming (FGP) model has been near to current situation and has shown realistic conditions according to expertise and advantage of this area in cultivation of certain crops. So the FGP model has desirability in each of indicators than other five models.